2011
DOI: 10.1002/app.35084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, thermal, and morphological properties of injection molded poly(lactic acid)/SEBS‐g‐MAH/organo‐montmorillonite nanocomposites

Abstract: Poly(lactic acid)/organo-montmorillonite (PLA/OMMT) nanocomposites toughened with maleated styrene-ethylene/butylene-styrene (SEBS-g-MAH) were prepared by melt-compounding using co-rotating twin-screw extruder followed by injection molding. The dispersibility and intercalation/exfoliation of OMMT in PLA was characterized using X-ray diffraction and transmission electron microscopy (TEM). The mechanical properties of the PLA nanocomposites was investigated by tensile and Izod impact tests. Thermogravimetric ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 29 publications
9
62
0
Order By: Relevance
“…In accordance with some other authors [27][28][29], good correlation has been found between toughness a t and PLA crystallinity CR m . Inverse proportionality has been found between stress at break ε b and PLA crystallinity CR m , similarly to [28]. Yield strain ε y shows inverse relation to PCL crystallization rate s i , which could be attributed to higher perfection of PCL crystallites attained at lower crystallization rates.…”
Section: Relation To Functional Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with some other authors [27][28][29], good correlation has been found between toughness a t and PLA crystallinity CR m . Inverse proportionality has been found between stress at break ε b and PLA crystallinity CR m , similarly to [28]. Yield strain ε y shows inverse relation to PCL crystallization rate s i , which could be attributed to higher perfection of PCL crystallites attained at lower crystallization rates.…”
Section: Relation To Functional Propertiessupporting
confidence: 90%
“…1) in comparison with about 10% crystallinity of neat PLA [9]. In accordance with some other authors [27][28][29], good correlation has been found between toughness a t and PLA crystallinity CR m . Inverse proportionality has been found between stress at break ε b and PLA crystallinity CR m , similarly to [28].…”
Section: Relation To Functional Propertiessupporting
confidence: 88%
“…Also, the thermal stability of PLA/NPCC nanocomposites increased marginally with the increasing loading of SEBS-g-MAH. Similar finding was also observed in our previous works on PLA/OMMT [14] and PA6/PP/organoclay nanocomposites [16]. Figure 3 shows the DSC thermograms of PLA and PLA/NPCC nanocomposites.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 88%
“…Maleic anhydride grafted styrene-ethylene/butylene-styrene copolymers (SEBS-g-MAH) has been used as polymeric compatibilizer, interfacial modifier and toughening agent. In our previous work, the impact strength, elongation at break and thermal stability of PLA/organo-montmorillonite nanocomposites was enhanced significantly by the addition of SEBS-g-MAH [14]. SEBS-g-MAH improved the dispersion of nano-magnesium hydroxide (MH) and interfacial adhesion in polypropylene/MH nanocomposites [15].…”
mentioning
confidence: 98%
“…[1,2] The characterization of mechanical properties in these materials is usually made by measuring macroscopic properties, [3] but macroscopic properties are mainly influenced by the microstructure and by the properties of the individual phases. [4,5] The purpose of this work will be to study the influence of microstructural parameters of multiphase materials on macrostructural behavior.…”
Section: Introductionmentioning
confidence: 99%